Nurse practitioners in rural California and AIDS - Lewis, C E; Miramontes, H (The Journal of the Association of Nurses in AIDS Care, 1999)
A random sample of nurse practitioners located in the 26 rural counties of California were surveyed to assess their experience with HIV-positive patients. Of those selected, 70.5% participated; of those interviewed, 65.5% had seen a patient with HIV infection in the past 12 months. Of those providing primary care, 85% had seen HIV-positive patients. Their specific practice activities ranged from simply assessing to making all critical decisions with regard to therapeutic regimes in consultation with AIDS experts. Their most frequent activities involved education and/or counseling and the provision of psychosocial support.